Epidemiology of smoking in the Medical course in Lages - Santa Catarina (Research, Society and Development, 2020)
Objective: the objective was to trace the epidemiological profile of medical students at the Universidade do Planalto Catarinense (UNIPLAC) in Lages / SC. Method: study of data obtained through a questionnaire applied to 94 students from August 2013 to December 2013. Results: the average age of the participants was 23.06 years, with a minimum of 19 years and a maximum of 39 years. 19.1% were smokers, of these 8.5% were daily smokers and 10.6% were occasional smokers. The average age of smoking initiation was 17.88 years. 22.3% started smoking at 18 years of age. The highest incentive to start using cigarettes was the influence of friends in 61.1%. 72.2% of academic smokers smoked up to 10 cigarettes a day, and 61.1% said they were interested in quitting. 38.9% described pleasure and 33.3% described reducing anxiety as a sensation of smoking exposure. Conclusion: the high prevalence of smokers among medical students shows the need to reinforce prevention and smoking cessation programs aimed at this population.